You are Here: Home

# Mathematicians! Can you figure this out? watch

Announcements
1. I will algebraically prove to you that 1=2.

1. Let a = b
2. Then a² = ab
3. a² + a² = a² + ab
4. 2a² = a² + ab
5. 2a² - 2ab = a² +ab - 2ab
6. Hence, 2a² - 2ab = a² - ab
This can be written as 2(a² - ab) = 1(a² -ab)
and cancelling the (a² - ab) from both sides gives 1=2.

Can figure out in which step the fallacy lies? First one to give me the correct answer, along with an explanation of why that step is invalid, gets a personal rating and a follow on TSR

2. Dividing by 0 gives an undefined result.

So you've said so , not 1=2, you can't cancel 0.
3. a^2-ab = 0, and you can't divide by 0.
4. The mistake lies in the last step. As a squared equals ab, a squared minus ab is equal to 0, so in the last step you are actually dividing by zero, which isn't defined.
5. Yeh what they said ^^

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: July 22, 2016
Today on TSR

### Exam Jam 2018

Join thousands of students this half term

### Solo - A Star Wars Story

Poll
Useful resources

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE